Strategic implications of asynchronous healthcare communication. (11th May 2004) - Wilson, E. Vance; Lankton, Nancy K.
Asynchronous online communication technologies are likely to cause major changes in the way patients and their healthcare providers communicate. Initially, these technologies will be applied to undemanding communication uses, such as requesting prescription refills. In the longer term, however, the technologies may provide strategic benefits to healthcare innovators. In this paper, we project changes that we expect to accompany the advent of asynchronous healthcare communication and propose several strategic opportunities that these changes will create.